Development of Medical Record With Extreme Programming SDLC - I Gusti Ngurah Suryantara; Johanes Fernandes Andry (IJNMT (International Journal of New Media Technology), 2018)
The XP (eXtreme Programming) model is best suited for the development of information systems projects that require rapid adaptation to changes that occur during application development compared to the SDLC Waterfall model. XP is also suitable for fewer team members and is in the same location in software development of medical record. Software development should be well planned, so that the software obtained quality and in accordance with the needs of users. The selection of the right framework will determine the success of software development, thus avoiding patchwork in application development. Step by step of research methods for medical record software are Planning, design, coding, testing and software increment. Studies conducted in this study include: library study, interviews, observation, document examination. Next do an analysis of the aplications made, and check the document to get a picture of the system created. This is done as an analysis and system design conducted by researchers. Selection of the right framework at the time of application development to bridge between the developer side and the user side, so that the developed application can be completed on time. In this research use eXtreme Prorgamming framework which focused on development of medical record, because eXtreme Programming more emphasis on software development and system design with CRC (Class Responsibility Collaborator). XP framework that every step always involves users, programmers, and parts of testing so that the applications created can be completed in a timely manner and in accordance with the needs of users. Index Terms— CRC (Class Responsibility Collaborator), eXtreme Programming (XP), Medical Record, System.